The impact of positive psychological resources on career success among academic staff in Sudan / Mohammed Mustafa Mohammed Yousif Fadul - Mohammed Mustafa , Mohammed Yousif Fadul (2020)
Career success is important in shaping individual vocation’s identity. Different individual will have various perceptions about their career accomplishment; whether they feel successful or otherwise. This research aims to investigate the impact of positive psychological resources on career success among academic staff in public universities in Sudan. This due to the importance of career success in contributing to both individual’s performance and organisational growth. The research is guided by protean career theory (PCT), conservation of resource theory (COR), and self-determination theory (SDT) for explaining the theoretical framework. On the other hand, the conceptual framework informed by protean career orientation (PCO) as an independent variable, career adaptability (CAA) and psychological capital (PsyCap) as mediator variables, academics’ career success as the dependent variable, and Islamic work ethics (IWE) as a moderator. Data were collected from 398 academic staffs who work in public universities in Sudan using a drop-off and pick-up survey method. Data were analysed by using Smart-PLS and PROCESS macro software. The results revealed that PCO, CAA, and PsyCap were significantly related to academics’ career success. Additionally, the results emphasised that CAA and PsyCap mediate the relationships between PCO and academics’ career success. However, the moderated-mediation of IWE is not found in through the career adaptability path. This research provides implications both theoretically and practically including to the leaders in the universities to recognise PCO and psychological resources as important attributes to increase the level of academics’ motivation, and strength in order to determine their career success. Finally, the limitations of this research are discussed, and the directions for future research are suggested.